Dimension effects in the relationship between eco-innovation andfirm performance: a European comparison - Madaleno, M. (2021)
This study investigates the effect of eco-efficiency actions on firm performance, considering both turnover and employment growth, in the European enterprises with different firm size classes. The sample includes 63303 firms from 13 different European Union countries. The main contributions of this work are the use of the most recent Community Innovation Survey (CIS) and the consideration of firms' size when analysing the relationship between the introduction of environmental benefits and firm performance. Using the ordinary least squares and simultaneous equation models the results showed that eco-innovations may affect negatively turnover growth as well as employment growth, a result which is not sensitive to firms' size. However, environmental benefits introduced in products, demanded by the end user, are sensitive to the different size class to which the enterprise belongs. Both human capital and the number of adopted eco-innovation strategies influence positively firm performance, revealing to be more sensitive to the firm size. Overall, policy makers should be aware of the size as an important driver, or conditioning factor, for firm performance when forcing firms to introduce policies regarding environmental benefits.